A case of mycetoma-like chromoblastomycosis in Qatar - Gawahir A. Ali (14777260) (2020)
Chromoblastomycosis is one of the neglected tropical mycoses associated with chronic infection of the skin and subcutaneous tissues. We report a case of 49-year-old patient originally from India presented with a mycetoma-like lesion in his right foot which was slowly progressing over three-year period. The diagnosis of chromoblastomycosis was confirmed following surgical excision and identification of the unique histological pathology of muriform bodies. The patient was subsequently treated with a prolonged course of oral itraconazole with a favorable outcome. The clinical presentations, assessment and management of the disease are outlined. Other Information Published in: IDCases License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.idcr.2020.e00853